(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Successful nature conservation requires engagement of diverse groups of stakeholders. Attracting attention of general public and engagement of local communities that underpin sustainable development are between the most important aspects of effective communications by environmental non-governmental organizations (ENGOs). In the modern world digital tools provide unprecedented opportunities for broadening reach of ENGO communications. In Latvia, many organizations including ENGOs use digital tools as a part of their communications mix. However, it is important to understand to what extent the power of digital strategies is utilised by these organisations. For this purpose, analysis of Latvian ENGO digital strategies was undertaken. The analysis involved evaluation of digital usage by top Latvian ENGOs in comparison to application of online communications tools by similar organizations in Western Europe and in the USA. It was found that while Latvian ENGOs actively use digital communications tools, in comparison with western organizations a range of approaches that make online strategies effective is still underutilised. This may generally reduce reach of the communications and their public appeal. Ultimately, underuse of opportunities provided by digital communication tools may weaken effectiveness of nature conservation at a regional scale. Thus, it is suggested to enhance digital communications taking an example from Western ENGOS by introducing more educational and engaging content in a variety of formats, ranging from audio to video materials. Detailed recommendations based on findings of present review are provided.